Enhancement of the production of aromatics and bio-syngas from microwave ex-situ pyrolysis based on Zn/Zr modified biochar and multi-catalysts. (15th December 2022) - Shi, Xiaopeng; Li, Pan; Wang, Xianhua; Song, Jiande; Fang, Shuqi; Chang, Chun; Pang, Shusheng
Abstract: The main purpose of this work was to explore the effect of metal modified biochar and multi-catalysts on improving the quality of products by microwave pyrolysis (MVP) of biomass. Single-component catalysts and multi-catalysts were prepared by Zn/Zr impregnation methods. The prepared catalysts were evaluated by XRD, BET, FT-IR and SEM. The properties, composition and product distribution of bio-oil and bio-syngas were analyzed. The results showed that ZSM-5 obtained more bio-oil (42.16 wt%) at the expense of gas product yield, and BC obtained the highest gas yield (43.10 wt%). Zn promoted the selectivity of aromatic hydrocarbons in bio-oil, Zr could effectively improve the yield of syngas and upgrading bio-oil, respectively. Zr-modified multi-catalyst was prepared, and the highest syngas yield (91.54 vol%) and aromatic hydrocarbon products were obtained. Among them, the selectivity of monocyclic aromatic hydrocarbons (MAHs) reached 21.82%. The mechanism of MVP of biomass under the effect of Zn/Zr modified different catalysts was proposed. The study has successfully demonstrated an approach for producing high-value bio-oil and bio-syngas from microwave multi-catalyst pyrolytic system. Highlights: Constructed a biomass microwave multi-catalytic pyrolysis system. Aromatics yield reached 55.88 wt% under the influence of Zn modified biochar. Bamboo char achieved the highest hydrogen yields of 50.93 vol%. The effect mechanism of different catalysts under microwave was proposed. MAHs selectivity reached 21.81% through Zr-modified multi-catalyst.